Prevalence of Obesity in Hail Region, KSA: In a Comprehensive Survey - Hussain Gadelkarim Ahmed; Ibrahim Abdelmajeed Ginawi; Abdelbaset Mohamed Elasbali; Ibraheem M. Ashankyty; Awdah M. Al-hazimi (Journal of Obesity)
Background. Obesity contributes significantly to morbidity and mortality rates worldwide. We, therefore, aimed to provide epidemiological data on the prevalence of obesity in Hail, Kingdom of Saudi Arabia (KSA). Methodology. Data were collected during cross-sectional survey which included 5000 Saudi selected from 30 primary health care centers (PHCs) in Hail Region. Results. The overall prevalence of obesity in Hail was 63.6%. Moreover, the prevalence of males was 56.2% and the prevalence of females was 71%. Conclusion. Obesity is prevalent in the Hail Region which necessitates urgent interventions including health education.